A comparison of strategies for state‐selective coherent Raman excitation. (2nd August 2021) - Stamm, Jacob A.; Dantus, Marcos
Abstract: We report on the theoretical and experimental evaluation of state‐selective bond activation for coherent Raman spectroscopy and control of chemical reactivity. We compare six different strategies for state‐selective activation using shaped broadband femtosecond laser pulses. Results for a pair of long pulses with different wavelengths are also considered. For each of these approaches, we report on their theoretical and experimental ability to excite a desired vibrational mode while minimizing excitation of other modes including harmonics. We find that the double parabola spectral phase function gives the most intense Raman excitation with 10 cm −1 selectivity with the lowest background. The sinusoidal phase function produces intense Raman excitation with high selectivity but gives a series of harmonic excitations which could hinder selectivity. Implications of this study on several fields ranging from sensing, to controlling chemical reactions, and selective excited state excitation by X‐ray pulses are discussed. Abstract : Strategies to generate trains of pulses capable of inducing selective stimulated Raman transitions are evaluated.